The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
22nd International Conference on Human-Computer Interaction With Mobile Devices and Services 2020
DOI: 10.1145/3379503.3403554
|View full text |Cite
|
Sign up to set email alerts
|

“I’d like an Explanation for That!”Exploring Reactions to Unexpected Autonomous Driving

Abstract: Autonomous vehicles are complex systems that may behave in unexpected ways. From the drivers' perspective, this can cause stress and lower trust and acceptance of autonomous driving. Prior work has shown that explanation of system behavior can mitigate these negative effects. Nevertheless, it remains unclear in which situations drivers actually need an explanation and what kind of interaction is relevant to them. Using thematic analysis of real-world experience reports, we first identified 17 situations in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 38 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Placebo-Control 4 [35,71,97,111] Placebo Study 12 [18,20,22,23,28,82,100,107,110,110] Acknowledge Placebo Effects as a Confound 11 [1,7,10,21,47,64,74,83,86,91,94,105] modalities. For example, one can adapt letter presentation in an E-reader to alpha oscillations; an indicator of workload in the electroencephalogram [55], reduce the number of interaction possibilities with the number of errors made by the user [45], or adapt the interface to the mood of the user [61].…”
Section: Category N Studiesmentioning
confidence: 99%
“…Placebo-Control 4 [35,71,97,111] Placebo Study 12 [18,20,22,23,28,82,100,107,110,110] Acknowledge Placebo Effects as a Confound 11 [1,7,10,21,47,64,74,83,86,91,94,105] modalities. For example, one can adapt letter presentation in an E-reader to alpha oscillations; an indicator of workload in the electroencephalogram [55], reduce the number of interaction possibilities with the number of errors made by the user [45], or adapt the interface to the mood of the user [61].…”
Section: Category N Studiesmentioning
confidence: 99%
“…In challenging and critical driving scenarios, intelligent vehicles are likely to make decisions that are confusing to end-users [1], [2], e.g., unexpectedly initiating a lane change. As a way to assist end-users, and to establish trust, explanation provisions have been put forward [3], [4], [5]. While explanations are considered helpful, we argue that they would not be effective in achieving the aforementioned goals if they are not provided in intelligible forms as obligated by the General Data Protection Right (GDPR) Article 12 1 .…”
Section: Introductionmentioning
confidence: 99%
“…of Computer Science, Umeå University, Sweden. Email: sule.anjomshoae@umu.se 3 Helena Webb is with the Dept. of Computer Science, University of Nottingham.…”
Section: Introductionmentioning
confidence: 99%
“…In manual driving, video-recorded situations with pedestrians are perceived as more hazardous and critical (Finn and Bragg, 1986;Borowsky and Oron-Gilad, 2013) especially when drivers are inexperienced. For automated driving, recent studies have shown that in situations with pedestrians, drivers have a high need for information regarding the system's behavior (Wiegand et al, 2020;Wintersberger et al, 2020). Around 70% of drivers in a thinking-aloud driving simulator study requested an explanation for the automated vehicle's stopping behavior in a situation where a child unexpectedly ran across the street (Wiegand et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For automated driving, recent studies have shown that in situations with pedestrians, drivers have a high need for information regarding the system's behavior (Wiegand et al, 2020;Wintersberger et al, 2020). Around 70% of drivers in a thinking-aloud driving simulator study requested an explanation for the automated vehicle's stopping behavior in a situation where a child unexpectedly ran across the street (Wiegand et al, 2020). When participants were asked to identify objects in videos of urban driving scenes that an automated vehicle should inform them about, high priority was given to pedestrians near or on the road (Wintersberger et al, 2020).…”
Section: Introductionmentioning
confidence: 99%